Self-reported Race/Ethnicity and Intraoperative Occult Hypoxemia: A Retrospective Cohort Study. (1st March 2022) - Burnett, Garrett W.; Stannard, Blaine; Wax, David B.; Lin, Hung-Mo; Pyram-Vincent, Chantal; DeMaria, Samuel; Levin, Matthew A.
Abstract : Background: Pulse oximetry is ubiquitous in anesthesia and is generally a reliable noninvasive measure of arterial oxygen saturation. Concerns regarding the impact of skin pigmentation and race/ethnicity on the accuracy of pulse oximeter accuracy exist. The authors hypothesized a greater prevalence of occult hypoxemia (arterial oxygen saturation [Sao 2 ] less than 88% despite oxygen saturation measured by pulse oximetry [Spo2 ] greater than 92%) in patients undergoing anesthesia who self-reported a race/ethnicity other than White. Methods: Demographic and physiologic data, including self-reported race/ethnicity, were extracted from a departmental data warehouse for patients receiving an anesthetic that included at least one arterial blood gas between January 2008 and December 2019. Calculated Sao 2 values were paired with concurrent Spo2 values for each patient. Analysis to determine whether Black, Hispanic, Asian, or Other race/ethnicities were associated with occult hypoxemia relative to White race/ethnicity within the Spo2 range of 92 to 100% was completed. Results: In total, 151, 070 paired Sao 2 –Spo2 readings (70, 722 White; 16, 011 Black; 21, 223 Hispanic; 8, 121 Asian; 34, 993 Other) from 46, 253 unique patients were analyzed. The prevalence of occult hypoxemia was significantly higher in Black (339 of 16, 011 [2.1%]) and Hispanic (383 of 21, 223 [1.8%]) versus White (791 of 70, 722 [1.1%]) paired Sao 2 –Spo2 readings ( P < 0.001 for both). In the multivariable analysis, Black (odds ratio, 1.44 [95% CI, 1.11 to 1.87]; P = 0.006) and Hispanic (odds ratio, 1.31 [95% CI, 1.03 to 1.68]; P = 0.031) race/ethnicity were associated with occult hypoxemia. Asian and Other race/ethnicity were not associated with occult hypoxemia. Conclusions: Self-reported Black and Hispanic race/ethnicity are associated with a greater prevalence of intraoperative occult hypoxemia in the Spo2 range of 92 to 100% when compared with self-reported White race/ethnicity. Abstract : Among 46, 523 patients with 151, 070 paired arterial oxygen saturation (Sao 2 )–oxygen saturation measured by pulse oximetry (Spo 2 ) intraoperative readings at a single center, the prevalence of occult hypoxemia (Sao 2 less than 88% despite concurrent Spo 2 greater than 92%) was significantly increased in patients self-reporting Black (2.1%) and Hispanic (1.8%) race/ethnicity compared with patients self-reporting White (1.1%) race/ethnicity. After adjusting for other clinical factors, Black or Hispanic race/ethnicity was independently associated with occult hypoxemia.